Identification Environmentally Friendly Fishing Gear Tools Based on the Code of Conduct for Responsible Fisheries at Aceh Barat Daya - Mutia Aprilla, Ratna; musiani, musiani; Chaliluddin, Chaliluddin; Djamani, Rianjuanda; Muhammad, Muhammad (Jurnal Kelautan dan Perikanan Indonesia, 2022)
Aceh Barat Daya is a land area of Aceh which is directly opposite the Indian Ocean. The fishing gear in Southwest Aceh Barat Daya includes; hand line fishing gear, long line fishing gear, tug line fishing gear, ring trawl fishing gear, beach trawl fishing gear, floating chart fishing gear, gill net fishing gear. The purpose of this study was to identify environmentally friendly fishing tools based on the Code of Conduct for Responsible Fisheries (CCRF). Data collection was carried out by interviewing fishermen using descriptive methods. This research was conducted in November 2021. The results of this study indicate that environmentally friendly fishing gear are; tuna longline, tug line, hand line, gill net, floating chart, ring trawler. While fishing gear that is less environmentally friendly are; Beach trawler.Keywords: Aceh, Aceh Barat Daya, CCRF, environmentally friendly, fishing gear